Reagerar grisar immunologiskt mot foderproteiner? - Haggård, Lisa (2008)
The aim of this study was to detect antibodies in swine serum against proteins in soy beans, wheat, oat and barley. Two methods were used: agar gel immunodiffusion test (AGID), and SDS-PAGE followed by immunoblotting. The sera examined originated (I) from piglets younger than one week (negative control), (II) pigs from a feed trial with soy bean in a herd with PMWS, and (III) pigs inoculated with Brachyspira hyodysenteriae and Escherichia coli after being fed with soy. The AGID-test was negative concerning all examined sera which were analysed against proteins in soy bean, wheat, oat and barley. In the experiment based on immunoblot antibodies were demonstrated within all three groups of examined pigs. The sizes of the protein fragments demonstrated were 20, 28, 45, 46, 47, 48 and 50 kDa. The pigs from the feed trial were divided into two groups. One group was fed conventional soy and the other group processed soy where the contents of antigenic substances had been minimized. The group of pigs fed with conventional soy formed twice as many bands in the blot as the group fed soy which had been processed. Two out of three piglets showed antibodies against soy which indicates that maternal antibodies against soy can be transferred by the colostrum.